Antioxidants of Natural Products - Mee Ree Kim (Antioxidants, 2021)
Antioxidant ingredients are known to contribute to the beneficial effects of natural products in health promotion as well as disease prevention by reducing oxidative stress, caused by reactive oxygen or nitrogen species, in biological systems [...]